A CFD Simulation of the Hydrodynamics of a Reactor with and without a Draft Tube - A. Ochieng; A. E. Lewis; H. Pearce (International Mineral Processing Congress, 2003)
"Hydrodynamics and mixing are fundamental to the operation of mineral process systems such as flotation cells and metal precipitation reactors. Hydrodynamic conditions influence phase mixing and mass transfer in a multiphase system, and these affect the overall performance of such a system. Detailed information on the effects of the hydrodynamics on the performance of agitated systems is still required for the design and optimal operation of hydrometallurgical systems, which are always multiphase. Computational fluid dynamics (CFD) techniques have been employed to study the hydrodynamics and mixing, most of which have focussed on the performance of axial and radial pumping impellers in agitated tanks. However, very little has been reported on the influence of a draft tube on the flow profile in such systems.CFD simulation of a stirred vessel centres on the way the impeller is modelled. Some of the most recent approaches to modelling an impeller are impeller boundary condition (IBC), snap shot, sliding grid (SG), multiple frame of reference (MFR) and inner outer (IO). The accuracy, with which these models predict experimental results and the corresponding computational demands, form the basis upon which the choice of an approach is made. Most of these approaches (IO, SG and MFR) address the key problem of the stirred tank modelling, namely, the simultaneous meshing of the rotating impellers and the stationary baffles. The MFR is computationally cheap and has been found to give predictions that compare well with experimental data.The CFD technique (code CFX4.4) has been employed in the present work to study the hydrodynamics in a mixing vessel stirred with either a Rushton turbine or a pitched blade impeller. The multiple frame of reference (MFR) approach has been used to model both impellers. A draft tube was used only in the Rushton turbine stirred vessel. The flow profiles for the impellers have been studied in three regions; below the impeller tip, at the middle of the tank, and near the liquid surface. The simulation results were compared with literature data obtained using a laser Doppler velocimetry in the three regions of the vessel, and it was found that the model predictions were better in the impeller region. There was a poor prediction of the experimental results in the region closer to the liquid surface; however, this was improved when the turbulence parameter (C2) in the k-e model was set to a higher value. The value of the impeller clearance at which the Rushton turbine generates an axial impeller type flow has been determined and it has been shown that, at this clearance, a draft tube can be used to enhance axial flow in a Rushton turbine stirred reactor."